2023
DOI: 10.1186/s40537-023-00804-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing classification efficiency with machine learning techniques for pattern matching

Abstract: The study proposes a novel model for DNA sequence classification that combines machine learning methods and a pattern-matching algorithm. This model aims to effectively categorize DNA sequences based on their features and enhance the accuracy and efficiency of DNA sequence classification. The performance of the proposed model is evaluated using various machine learning algorithms, and the results indicate that the SVM linear classifier achieves the highest accuracy and F1 score among the tested algorithms. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It was observed that SVM performed well with the CKSAAP feature in comparison to other models (Supplementary Table S1). Due to good generalization ability, SVM has been effectively used in numerous classification problems [78][79][80]. Thus, the SVM-based CKSAAP model was selected as the final prediction model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that SVM performed well with the CKSAAP feature in comparison to other models (Supplementary Table S1). Due to good generalization ability, SVM has been effectively used in numerous classification problems [78][79][80]. Thus, the SVM-based CKSAAP model was selected as the final prediction model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is being used by many sectors to extract pertinent data from accessible datasets. A wide variety of algorithms have been developed to enable computers to learn on their own, with the primary goal of machine learning being the extraction of knowledge from available data [2][3][4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Osisanwo F.Y. et.al [5]. compares various supervised machine learning algorithms for classification.…”
mentioning
confidence: 99%